Turkey-Malaysia relations in the 21st Century - Durmaz, Ferhat; Mohamad Shukri, Syaza Farhana (DergiPark Akademik, 2019)
Although the connection between the Turks and Malays could be traced back to the 1500s, relations generally remained static until 2000. In the 21st century, relationships have started to develop in a multidimensional way in the political, economic and cultural spheres. The article concluded that the progress in Turkey-Malaysia relations in the 2000s is closely related to the changes in the foreign policy of the two countries. Another result of this work is that the actors do not put forth a strong political will to further develop relations in practice.